A paradoxical perspective on technology renewal in digital transformation. (18th August 2020) - Wimelius, Henrik; Mathiassen, Lars; Holmström, Jonny; Keil, Mark
Abstract: To realize their strategic goals and maintain a competitive advantage in the digital era, organizations must periodically renew their digital platforms and infrastructures. However, knowledge about such technology renewal is scattered across diverse research streams, so insights into the process are both limited and fragmented. In this article, we consolidate insights from previous research to conceptualize technology renewal as an inherently paradoxical digital transformation process that requires organizations to simultaneously remove their technological foundation and build on the practices that depend on it to implement a new technological foundation. Previous research suggests that technology renewal initiatives are driven by three paradoxical tensions: (a) established vs renewed technology usage, (b) deliberate vs emergent renewal practices and (c) inner vs outer renewal contexts. We apply this framing to a longitudinal case study in which we analyse and explain how an organization's responses to manifestations of these tensions eventually led to a vicious cycle of continued investments into two overlapping and largely incompatible digital platforms over a 9‐year period. Based on these conceptual and empirical insights, we theorize technology renewal as a paradoxical, and increasingly critical, digital transformation process that forces managers to make decisions in complex and ambiguous choice situations.